PREDICTION MODEL OF OBESITY AMONG TEACHERS IN SENIOR HIGH SCHOOL IN KENDARI - La Banudi; Wenny Ino Ischak; Suriana Koro; Purnomo Leksono (Belitung Raya Foundation, Indonesia, 2018)
Background: Obesity that occurs in adolescents (age >18 years) shows a significant increase, from 12% in 2007 to 13% in 2010 and 19% in 2019 in males, and from 13% to 28% in 2013 in females. Objective: To analyze the prediction model of obesity among teachers in senior high school in Kendari, Indonesia. Methods: This was a prediction cross-sectional study. There were 250 high school teachers were recruited from 12 senior high schools using a purposive sampling. The instruments used were questionnaires (food frequency, consumption recall, and activities recall questionnaire), Seca weight scale, anthropometry microtoice, meter, computer program, and stationery. Data were analyzed using Chi-Square. Results: Findings showed that there was a significant correlation between age group (p = 0.05), knowledge (p= 0.02), stress (p= 0.05) and diet (p= 0.013). The prediction factor of obesity among high school teachers was that teachers with an upper age (age> 45 years) were likely to be obese 2.64 times than teachers at a young age (age <45 years). If teachers experienced stress, they would suffer from obesity 2.17 times compared with teachers with no stress. Conclusion: Factors associated with obesity in high school teachers in Kendari Indonesia were age, knowledge, stress and dietary factors. Factors that were not related with obesity were attitudes about nutrition, activity and smoking habits. The highest predictors of obesity were age and stress.